Pemanfaatan Kotoran Kambing sebagai Bahan Bakar Renewable (Gas Bio) untuk Menghindari Pencemaran Lingkungan di Desa Binangun Kecamatan Banyumas Kabupaten Banyumas - S.A.C. Luthfi Luthfi; R. Fitria; N. Hindratiningrum (Bulletin of Applied Animal Research, 2021)
The problem faced by the "Sida Maju 1" and "Tangkas Farmers" in Binangun Village is the handling of waste that is not handled properly because the maintenance process is only piled up and of course causes environmental pollution. The purpose of this activity is to utilize the business waste belonging to the group members into a renewable energy source in the form of biogas. The method used is a consultation method that begins with an approach, then is given counseling, training and coaching and finally continuous evaluation and monitoring from the program implementer. The results of this activity are (1) knowledge, attitudes and skills to become livestock in terms of utilizing bio gas dung which can be seen from the increase in the post test value compared to the pretest by 81%; (2) the biogas produced can light the stove for 7 minutes. The conclusion of this activity is the skills of farmers in utilizing waste into useful materials. Suggestions that can be submitted is to increase the population of goats owned by members so that the volume of gas produced is greater so that its utilization is more optimal. Â  Keywords: goat manure, bio gas